Explorative and exploitative strategies and export performance: The moderating effects of entrepreneurial orientation. Issue 1 (29th November 2019) - Khalid, Saba
Abstract : Purpose: This study aims to examine the moderating effects of entrepreneurial orientation (EO) on the relationship of exploitation and exploration strategies with export performance. Drawing on the current literature, this conceptual paper develops a framework that first links the exploitative and explorative strategies with the export performance. Later, propositions are developed to indicate different combinations of individual dimensions of EO as moderating factors to this relationship. Design/methodology/approach: This is a conceptual paper which builds on prior conceptual and empirical management research. Findings: The preliminary conceptual findings suggest that the exploitative strategy is valuable in the short run after new entry, while explorative strategy is significant in the long run only after new entry. For the moderating effects, a combination of high innovation, high proactiveness and high risk-taking may positively influence both the strategies with export performance. While low innovativeness but high proactiveness and high risk-taking is assumed to positively moderate the exploitative strategy and export performance relationship, a negative moderating role is seen for explorative strategy and export performance. Similarly, high innovativeness but low risk-taking and low proactiveness will negatively moderate the relationship between exploitative/explorative strategy and export performance. Originality/value: The current literature warrants research on this topic. For example, literature lacks studies regarding a better understanding of the impact of export market exploitation and exploration on export performance. Further, the impact of EO on performance is well acknowledged in the literature, but their relative influence on the performance of exporting firms remains inconclusive.